Problematika Heterogenitas Latar Belakang Pendidikan dalam Pembelajaran Bahasa Arab di Ma’had Al Ihsan Surabaya - Dinda Lukmana, Reksi; Nadlir, Nadlir; Wafa , Ali (STAI Ali bin Abi Thalib Surabaya, 2024)
This study aims to describe (1) the problems of learning Arabic caused by the heterogeneity of the educational background of the students, (2) the problems experienced by non-Islamic boarding school students in the learning process and their efforts to achieve the target of learning Arabic, and (3) the efforts teachers address the problems that occur in the process of learning Arabic. The method used in this research is descriptive qualitative type. The subjects in this study were two Ma'had Al Ihsan Surabaya teachers and six new students. The background of this research is that there are problems experienced by several new students of Ma'had Al Ihsan Surabaya, especially non-Islamic boarding school students, in the process of learning Arabic in class. The results showed that (1) the various educational backgrounds of the students greatly influenced the level of quality of their understanding of Arabic lessons (2) the constraints of non-Islamic boarding school students in mastering Arabic, which consisted of factors of interest, educational background, difficulties in adjusting, delays in learning, lack of confidence, laziness and anxiety. As for the efforts made by non-Islamic boarding school students to be able to achieve the target of learning Arabic, namely studying with friends and increasing study time outside class hours (3) efforts made by ustadz to strengthen students' ability to speak, namely forming study groups both in class and outside outside of class, holding additional classes, holding additional activities every Saturday morning, giving additional assignments and creating a mandatory environment in Arabic.